145 PREDICTION OF NEW ONSET ATRIAL FIBRILLATION IN PATIENTS WITH ACUTE CORONARY SYNDROME UNDERGOING PERCUTANEOUS CORONARY INTERVENTION USING THE C2HEST AND MC2HEST SCORES A REPORT FROM THE MULTICENTER REALE-ACS REGISTRY. (15th December 2022) - Gelfusa, Martina; Biccirè, Flavio Giuseppe; Tanzilli, Gaetano; Prati, Francesco; Sammartini, Emanuele; Celeski, Mihail; Budassi, Simone; Barillà, Francesco; Lip, Gregory Y H; Pastori, Daniele
Abstract: Aims: New onset atrial fibrillation (NOAF) is associated with worse clinical outcomes after acute coronary syndrome (ACS). Identification of patients at risk of NOAF remains challenging, and various clinical scores of varying complexities have been proposed to predict incident AF. We tested the value of the simple C2 HEST score for predicting NOAF in patients with ACS. Methods: We studied patients from the prospective ongoing multicenter REALE-ACS registry of patients with ACS. NOAF was the primary endpoint of the study. The C2 HEST score was calculated as coronary artery disease or chronic obstructive pulmonary disease (1 point each), hypertension (1 point), elderly (age ≥75 years, 2 points), systolic heart failure (2 points), thyroid disease (1 point). We also tested the mC2 HEST score. Results: We enrolled 555 patients (mean age 65.6±13.3 years; 22.9% women), of which 45 (8.1%) developed NOAF. Patients with NOAF were older (p<0.001) and had more prevalent hypertension (p=0.012), COPD (p<0.001) and hyperthyroidism (p=0.018). Patients with NOAF were more frequently admitted with STEMI (p<0.001), cardiogenic shock (p=0.008), Killip class ≥2 (p<0.001) and had higher mean GRACE score (p<0.001). Patients with NOAF had a higher C2 HEST score compared with those without (4.2±1.7 vs 3.0±1.5, p<0.001). A C2 HEST score >3 was associated with NOAF occurrence (odds ratio 4.33, 95% confidence interval 2.19-8.59, p<0.001). ROC curve analysis showed good accuracy of the C2 HEST score (AUC 0.71, 95%CI 0.67-0.74) and mC2 HEST score in predicting NOAF (AUC 0.69, 95%CI 065-0.73). Conclusion: The simple C2 HEST score may be a useful tool to identify patients at higher risk of developing NOAF after presentation with ACS.